2022
DOI: 10.1002/jcph.2119
|View full text |Cite
|
Sign up to set email alerts
|

Using Endogenous Biomarkers to Derisk Assessment of Transporter‐Mediated Drug‐Drug Interactions: A Scientific Perspective

Abstract: Comprehensive characterization of transporter mediated drug‐drug interactions (DDIs) is important to formulate clinical management strategies and ensure the safe and effective use of concomitantly administered drugs. The potential of a drug to inhibit transporters is predicted by comparing the ratio of the relevant concentration (depending on the transporter) and the half maximum inhibitory concentration to a predefined “cutoff” value. If the ratio is greater than the cutoff value, modeling approaches such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…This conclusion is based on the integrated interpretation of the biomarkers (NMN and IBC) and sumatriptan (a selective OCT1 probe drug) data. [25][26][27] The coadministration of a single 400-mg dose (approximates steady-state ritlecitinib systemic exposures with 200 mg once daily) of ritlecitinib increased the AUC inf of sumatriptan by ≈30%-50% relative to sumatriptan dose given alone. As the maximum increase in sumatriptan exposure is 115% as observed in carriers of 2 deficient OCT1 alleles, 7 the inhibition effect of ritlecitinib is considered moderate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is based on the integrated interpretation of the biomarkers (NMN and IBC) and sumatriptan (a selective OCT1 probe drug) data. [25][26][27] The coadministration of a single 400-mg dose (approximates steady-state ritlecitinib systemic exposures with 200 mg once daily) of ritlecitinib increased the AUC inf of sumatriptan by ≈30%-50% relative to sumatriptan dose given alone. As the maximum increase in sumatriptan exposure is 115% as observed in carriers of 2 deficient OCT1 alleles, 7 the inhibition effect of ritlecitinib is considered moderate.…”
Section: Discussionmentioning
confidence: 99%
“…This phase 1, open‐label study in healthy adults demonstrated that ritlecitinib is an inhibitor of OCT1 but not OCT2 or MATE1/MATE2K in vivo. This conclusion is based on the integrated interpretation of the biomarkers (NMN and IBC) and sumatriptan (a selective OCT1 probe drug) data 25–27 . The coadministration of a single 400‐mg dose (approximates steady‐state ritlecitinib systemic exposures with 200 mg once daily) of ritlecitinib increased the AUC inf of sumatriptan by ≈30%‐50% relative to sumatriptan dose given alone.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, novel tools that overcome the complexity and better predict BCRP-mediated DDI are needed. The use of endogenous biomarkers to assess transporter-mediated DDI has been growing substantially in the last decade, in part driven by an industrial need to develop methodologies to detect and predict transporter DDIs in early phase I clinical trials and regulatory demands to improve the traditional static mechanistic models that often give conservative predictions with many undesirable false negatives (Chu et al, 2018, Muller et al, 2018, Mochizuki et al, 2021, Arya et al, 2022. The past decade of biomarker investigation has yielded great advances in the development of sensitive, selective and predictive endogenous probes for hepatic organic anion transporting polypeptides (OATP) 1B1 and OATP1B3 (e.g., coproporphyrin I) (Lai et al, 2016 DMD-AR-2023-001284 Shen et al, 2016), renal organic anion transporter (OAT) 1 and OAT3 (e.g., pyridoxic acid) (Shen et al, 2018, Shen et al, 2019, Willemin et al, 2021, and multidrug and toxin extrusion protein (MATE) 1 and MATE2-K (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…N-methylnicotinamide and creatinine) (Ito et al, 2012, Muller et al, 2015, Chu et al, 2016, Mathialagan et al, 2021. These endogenous biomarkers have enormous potential to better monitor transport activity and assess transporter DDI risk (Chu et al, 2018, Arya et al, 2022. However, there are limited studies on the endogenous substrates of BCRP, and endogenous biomarkers of BCRP have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still significant challenges to use in vitro data to predict transporterrelated perpetrator DDIs due to the limitations of in vitro transporter inhibition assays and gaps in in vitro to in vivo extrapolation (IVIVE) (Chu et al, 2017). Therefore, in recent years, there has been a tremendous interest and progress in identifying, characterizing, and applying endogenous biomarkers to access DDI potential for hepatic and renal transporters in early clinical trials (Chu et al, 2018;Rodrigues et al, 2018;Mochizuki et al, 2021;Arya et al, 2022). Among all, several classes of endogenous substrates of OATP1B demonstrated the potential to serve as surrogate clinical probes to assess DDIs.…”
Section: Introductionmentioning
confidence: 99%